Teachers’ Perceptions on Effective Resilience Strategies to Challenging Teaching Space in Tanzania: A Study of Selected Secondary Schools in Morogoro Municipality - Costantine, Edgar; Mwinjuma, Juma Saidi; Nemes, Joyce (Journal of Multidisciplinary Research and Development, 2025)
This study investigates the perceptions of teachers regarding effective resilience strategies in challenging educational environments within secondary schools in Morogoro Municipality, Tanzania. Grounded in Pelidores’ Resilience Theory and Conservation Resource Theory, the research highlights the importance of social interactions and resource management in fostering teacher resilience. Utilizing a mixed-methods approach, data were collected from 236 participants, including 234 teachers and 2 key informants, through simple random and purposive sampling techniques. Findings reveal a complex landscape of perceptions, with many teachers expressing skepticism about the effectiveness of various resilience strategies, particularly in creating positive school cultures and fostering supportive relationships. While some strategies, such as positive verbal reinforcement and interactive learning, received favorable evaluations, a majority of respondents rated these approaches as inadequately implemented. This suggests a significant gap between recognizing the value of resilience strategies and their practical applicability. The study underscores the need for targeted interventions, including professional development programs, mentorship networks, and policies that prioritize teacher well-being and resource allocation. By addressing these challenges and fostering a supportive educational environment, the resilience of teachers can be significantly enhanced, ultimately leading to improved educational outcomes for students.